PENGARUH PENAMBAHAN TEPUNG DAUN KATUK (Saoropus Androginus L. Merr) TERHADAP NILAI ORGANOLEPTIK DAN NILAI GIZI BISKUIT BERBASIS SAGU (Metroxylon Sagu Rottb) - Sariani, Sariani; Karimuna, La; Ansharullah, Ansharullah (Jurnal Sains dan Teknologi Pangan, 2019)
BSTRACT This study aims to study the effect of katuk leaf flour addition to the organoleptic value and nutritional value of sago-based biscuits that the panelists liked. This study used a completely randomized design (CRD) with a comparison formulation between sago flour and katuk leaf flour, namely K0 (100% sago flour), K1 (98% sago flour : 2% katuk leaf flour), K2 (96% sago flour : katuk leaf flour 4% ), K3 (sago flour 94% : katuk leaf flour 6%). Data were analyzed using variance Analysis of Variances (ANOVA). The addition of katuk leaf flour showed a very significant effect (p <0.05) on the organoleptic test of color, aroma, taste and texture. The results of the research on selected sago biscuit products based on organoleptic assessment were treatment K1 (98% sago flour : 2% katuk leaf flour) with color preference rating score 3.70 (likes), aroma 3.67 (likes), flavor 3.80 (likes), and texture 3.53 (likes) and analysis of the content of nutritional values including moisture, ash, protein, fat, and carbohydrates with values of 2.77%, 2.05%, 16.48%, 23.70% and 55% respectively. Based on the results of the analysis of the nutritional value of biscuits on carbohydrate and fat components not yet fulfilling SNI, but based on organoleptic assessment, panelists were accepted (preferred). Keywords : Sago biscuits, sago flour, katuk leaf flour ABSTRAK Penelitian ini bertujuan untuk mempelajari pengaruh penambahan tepung daun katuk terhadap nilai organoleptik dan nilai gizi biskuit berbasis sagu yang disukai panelis. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan formulasi perbandingan antara tepung sagu dan tepung daun katuk, yaitu K0 (tepung sagu 100%), K1 (tepung sagu 98% : tepung daun katuk 2%), K2 (tepung sagu 96% : tepung daun katuk 4%), K3 (tepung sagu 94% : tepung daun katuk 6%). Data dianalisis menggunakan sidik ragam Analysis of Variances (ANOVA). Penambahan tepung daun katuk menunjukkan pengaruh yang sangat nyata (p <0,05) pada uji organoleptik warna, aroma, rasa, dan tekstur. Hasil penelitian produk biskuit sagu terpilih berdasarkan penilaian organoleptik adalah perlakuan K1 (tepung sagu 98% : tepung daun katuk 2%) dengan skor penilaian kesukaan terhadap warna 3.70 (suka), aroma 3.67 (suka), rasa 3.80 (suka), dan tektur 3.53 (suka) serta analisis kandungan nilai gizi meliputi kadar air, abu, protein, lemak, dan karbohidrat dengan nilai berturut-turut 2.77%, 2.05%, 16.48%, 23.70%, dan 55%. Berdasarkan hasil analisis kandungan nilai gizi biskuit pada komponen karbohidarat dan lemak belum memenuhi SNI namun berdasarkan penilaian organoleptik dapat diterima (disukai) panelis. Kata kunci : Biskuit sagu, tepung sagu, tepung daun katuk